Production diagnosis for organic vegetables of family farming associations of the southern Minas Gerais state, Brazil - Dias Netto, Eusebio de Souza; Marques, Douglas José; Bianchini, Hudson Carvalho (Science & Technology Journals, 2020)
The objective of this work was to evaluate general aspects of the associations of organic producers of the southern Minas Gerais state, Brazil. This region is one of the largest producers of vegetables in the country. In recent years, facing the need of a differential in production to serve the consumer market, many producers opted for the organic production of vegetables, aiming to offer a healthier and more rentable product. The objective of this study was to evaluate the general aspects of certified organic producer associations of southern Minas Gerais state, Brazil. The research was based on the data collection from the agents involved in the scenario of organic vegetable production in that region. A representative group sampling with 96 producers was used; they are part of 12 associations registered in the organization of organic producers. The analyses show the following results: the average age of the producers is 50.4 years, in which, therefore, older individuals predominate; the majority of farmers (65.63%) owns the production areas; the associations Ecominas, Abal, and OAV are those that possess the largest areas of organic production; crops with the highest production are tomato, yam, potato, sweet potato, and lettuce; and the most used form of marketing is the direct sale to the consumer.